2022
DOI: 10.1038/s41419-022-04563-9
|View full text |Cite
|
Sign up to set email alerts
|

HBx increases chromatin accessibility and ETV4 expression to regulate dishevelled-2 and promote HCC progression

Abstract: Hepatitis B virus (HBV) infection is the predominant causes of hepatocellular carcinoma (HCC). HBV X protein (HBx), as the most frequently integrated viral gene sequence following HBV infection, plays a critical role in the pathogenesis of HCC. H3K27ac is a characteristic marker for identifying active enhancers and even indicates chromatin accessibility associated with super-enhancers (SEs). In this study, H3K27ac ChIP-seq was applied for high-quality SE annotation of HBx-induced SEs and chromatin accessibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Previous studies have proven that NQO1, ETV4, BSG, and HMGA1 are highly expressed in HCC ( Jin et al, 2019 ; Teng et al, 2019 ; Yang et al, 2021 ; Zheng et al, 2022 ). In addition, the upregulation of PBK, BIRC5, PLK1, and EZH2 was also validated in HCC tissues ( Xiao et al, 2019 ; Yang et al, 2019 ; Tian et al, 2020 ; Huang et al, 2021 ; Lin et al, 2021 ; Peng et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have proven that NQO1, ETV4, BSG, and HMGA1 are highly expressed in HCC ( Jin et al, 2019 ; Teng et al, 2019 ; Yang et al, 2021 ; Zheng et al, 2022 ). In addition, the upregulation of PBK, BIRC5, PLK1, and EZH2 was also validated in HCC tissues ( Xiao et al, 2019 ; Yang et al, 2019 ; Tian et al, 2020 ; Huang et al, 2021 ; Lin et al, 2021 ; Peng et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that NQO1 is upregulated and promotes an aggressive phenotype in HCC ( Shimokawa et al, 2020 ; Yang et al, 2021 ; Wang et al, 2022 ). Zheng et al reported that the enhanced expression of ETV4 by HBx may stimulate the metastasis of HCC ( Zheng et al, 2022 ) The literature showed that the interaction between ETV4 and YAP conferred a growth advantage to HCC and had a protumorigenic role ( Xu et al, 2022 ). Some studies have shown that BSG and HMGA1 play significant roles in the development and progression of HCC ( Li et al, 2015 ; Jin et al, 2019 ; Teng et al, 2019 ; Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…HBV‐encoded HBx is an oncogenic protein which could regulate gene transcription 29 . HBx can promote the expression of ETV4 to enhance the invasion and metastasis of HCC cell 30 . HBx also can negatively regulate p53 transcriptional activity to promote cell proliferation 7 .…”
Section: Discussionmentioning
confidence: 99%
“…29 HBx can promote the expression of ETV4 to enhance the invasion and metastasis of HCC cell. 30 HBx also can negatively regulate p53 transcriptional activity to promote cell proliferation. 7 In this study, we found that HBx inhibits the transcription of DCN by interfering the activity of p53.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 As manifested in clinical practices, hepatitis viral infection is also a critical reason contributing to the poor prognosis of HCC. 3 However, recent studies have reported that infection of the hepatitis virus may contribute to a better response to immunotherapy in HCC patients. 4,5 It is necessary to take viral infection into consideration of evaluating the response to immunotherapy, which is also crucial for treatment strategies in HCC patients.…”
Section: Introductionmentioning
confidence: 99%